A Web Based Optimization System Using Goal Programming for Supply Chain Network - Alp Ustundag; Aysenur Budak; Peiman Alipour Sarvari; Mahir Oner (International Journal of Supply Chain Management, 2014)
Considering high competitive nature of todays industries,being on plan is very vital for supply chain network of an organization. Allthe flows of materials from initial suppliers to final customers need to besmooth. Hence, distribution network design is an important strategic decisionproblem for the supply chain managers. The aim of this research is to propose a web-based Decision Support System (DSS) foroptimizing fuzzy distribution network in the context of supply-chain management. A fuzzy goal-programming model has been designedfor the proposed DSS to consider the uncertain and imprecise data. Thisresearch focuses on four conflict fuzzy goals of (i). all demands must be covered by distribution center, (ii).investment goals for opening new sites considering fix costs, (iii). Investmentgoals for opening new distribution centers considering fix costs, (iv). Supplycosts goals, to meet the optimized results. Hence with those attributes ofmembership function of goals, the decision makers can apply this model toobtain the investment policy and the achieved level of each individual goal.